2005
DOI: 10.3758/bf03193178
|View full text |Cite
|
Sign up to set email alerts
|

Does satiation close the open economy?

Abstract: Pigeons responded on fixed-interval and fixed-ratio food schedules during sessions of extended duration. Pause lengths from the beginning of the session, when the subjects were hungry, resembled those found in open economies, whereas pause lengths from the end of the sessions, when the subjects were close to satiation, resembled those from closed economies. A model of motivation captured key features of the data, suggesting that a changing level of hunger is a causal factor in the behavioral differences observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 49 publications
0
15
1
Order By: Relevance
“…Although session length per se may not be a factor in determining differential patterns of behavior across economy types (Hall & Lattal, 1990), the ability of the animal to reach satiation in a single session may account for many of the reported differences in behavior. In a recent review and empirical study of open and closed economies, Posadas‐Sanchez and Killeen (2005) demonstrated that it was possible to obtain patterns of responding consistent with open economies in the beginning portion of a closed economy in which the animals began deprived, whereas the remainder of the session more closely resembled a closed economy. From these and other data, they concluded that satiety is a crucial factor in determining the degree of openness of an economy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although session length per se may not be a factor in determining differential patterns of behavior across economy types (Hall & Lattal, 1990), the ability of the animal to reach satiation in a single session may account for many of the reported differences in behavior. In a recent review and empirical study of open and closed economies, Posadas‐Sanchez and Killeen (2005) demonstrated that it was possible to obtain patterns of responding consistent with open economies in the beginning portion of a closed economy in which the animals began deprived, whereas the remainder of the session more closely resembled a closed economy. From these and other data, they concluded that satiety is a crucial factor in determining the degree of openness of an economy.…”
Section: Resultsmentioning
confidence: 99%
“…Along the continuum, a number of factors such as the time to extrasession feeding, session length, and deprivation may vary, and the openness of the economy will vary accordingly (Hursh, 1984; Timberlake, Gawley, & Lucas, 1987). These factors, individually or collectively, can contribute to differences in behavior generated by economy types (Foster et al, 1997; Posadas‐Sanchez & Killeen, 2005; Timberlake & Peden, 1987).…”
mentioning
confidence: 99%
“…For example, response rates on ratio schedules can be described by the economic demand curve in which ‘consumption’ (reinforcement rate) is plotted against ‘price’ (ratio) (see Bickel et al 1995 ; Johnson and Bickel 2006 ). The concept of elasticity of demand captures some, but not all, of the behavioural effects of reinforcers that are accounted for in terms of a in the present model (Killeen 1995 ; Posadas-Sánchez and Killeen 2005 ). We make no claim that the present model is intrinsically preferable to models based on other theoretical approaches.…”
Section: Discussionmentioning
confidence: 99%
“…After reforming the supply side and adjusting the production capacity structure, although the problem of overcapacity has not been fundamentally solved, the utilization level of China's industry and major industries has improved. To further improve the ecological environment, it is necessary to eliminate the "zombie enterprises" with little remaining development space and debts as soon as possible and to rectify those industries with high governance costs, high investment, and low output [28][29][30]. At this stage, China's economic development has slowed down markedly, the international environment has changed significantly, and many enterprises have experienced a significant decline in their operating levels.…”
Section: Suggestionsmentioning
confidence: 99%